DARI SKRIPTORIUM KE ARSIP DIGITAL: TRANSFORMASI FILOLOGI AL-QUR’AN DI ERA TEKNOLOGI: Dari Skriptorium ke Arsip Digital: Transformasi Filologi Al-Qur’an di Era Teknologi - Nisa, Lia Khoirotun; Mufid, Abdul; Syaiful, Muhammad (jsd: Journal of Society and Development, 2025)
The digitalization of Qur’anic manuscripts has emerged as a central discourse in modern philology, reshaping the mechanisms of preservation, transmission, and textual analysis. This article aims to critically examine the transformation of Qur’anic philology from the traditional scriptoriumlong regarded as an authoritative space for manuscript copying and the verification of textual variants towards a technologically mediated ecosystem of open-access digital archives. Employing a descriptive-analytical approach, this study reviews historical literature, evaluates major Qur’anic manuscript digitalization projects, and analyzes the use of databases and computational tools in textual criticism. The findings reveal that digitalization not only broadens access to manuscript preservation but also triggers an epistemological shift in philological practice, particularly in relation to textual authority, verification of variant readings, and models of scholarly collaboration. Furthermore, the study identifies the necessity of rearticulating classical philological principles into digital frameworks to preserve Isnād integrity and support rigorous Tahqīq practices. The primary contribution of this article is the formulation of a conceptual framework for Qur’anic digital philology that bridges the values of the classical scriptorium with the affordances of digital technology, providing a theoretical and methodological foundation for Qur’anic manuscript studies in the technological era.